Attitude System in Online Newspaper Articles Written by Female and Male Authors - Fitriani, Walida Wahid; Rukmini, Dwi; Pratama, Hendi (The Journal of Educational Development, 2020)
An appraisal is the developmental theory of Halliday's interpersonal meaning proposed by Martin & White (2005). There are three systems in Appraisal namely attitude, engagement, and graduation. This study investigated the comparison of attitude manifested in online newspaper articles written by female and male authors. It was intended to reveal the realization, similarities, and differences in the attitude system in the articles. It employed a descriptive qualitative method in the form of discourse analysis to examine sixteen online newspaper articles within the theoretical framework of Appraisal (Martin & White, 2005). Besides, the gender and psychological theories of Shields (2000) and Guimond (2008) were employed. The findings of this study found out that both authors displayed three subsystems of attitude. Then, appreciation items were dominantly perceived. On the other side, affect became a significant gap of differences between female and male authors. This study is very beneficial for English language learners to pay more attention to the use of appraisal in their writings. They can convey their voices and emotions effectively by using Appraisal.